Asuhan Kebidanan Komprehensif Pada Ny.S Umur 17 Tahun dengan Resiko Tinggi Umur dan Kekurangan Energi Kronik (KEK) di Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Siti Janatur Rohmah; Himatul Khoeroh; Khunelis Khunelis (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Pregnancy risk factors that cause complications and maternal mortality are high risk at age ≤ 20 years and chronic energy deficiency. The pregnancy rate for pregnant women ≤ 20 years old at Bumiayu Health Center in 2022 was 7 cases, while the incidence of SEZ at Bumiayu Health Center in 2022 was 56 cases. One of the efforts to reduce the high risk factors of age ≤ 20 years and SEZ by providing comprehensive care. This study used a qualitative descriptive method with a case study approach, data collection using interviews, physical examinations, supporting examinations, obstetric examinations, observations, documentation studies, literature studies and literature. The main informant is Mrs.S and additional informants are midwives and husbands. Based on the results of comprehensive midwifery care performed on Mrs.S during pregnancy Mrs.S found the problem that TFU was not in accordance with gestational age.